Kontribusi Metode Neuro-Linguistic Programming Terhadap Kemampuan Goal setting Pelarl cepat 100 Meter Perorangan - Miftakhul Jannah (LPPM Universitas Proklamasi 45, 2012)
This research was designed to test the contribution of the Neuro-Linguistic Programming (NLP) to individual 100 meters sprinters' goal setting ability. There were fourteen individual 100 meters sprinters from Training Center Local of East Java participated in this research Data were analyzed using difference mean pretest and posttest goal setting ability score The result obtained indicated that: (1) The mean pretest goal setting ability score = 6. (2) The mean postest goal setting ability score = 12.5 (3). The mean gain score = 6 5 There vvas signrficat difference individual 100 meters spnntors' goal setting ability between before and after received the NLP training Aftor receiving the NLP training, the individual 100 meters sprinters' goal setting ability was increased. Individual 100 meters sprinters' ability increased through the NLP training because of subject's readiness and participation, training methods and training Hems, with they are interrelated to each other.